CHILDREN’S FEARS: FEATURES OF EXPRESSION IN PARTICULAR FAMILIES - Borshchova, Tetyana Olexandrivnaс; Krupnyk, Ivan Romanovych (Insight: the psychological dimensions of society, 2019)
Purpose. Given the importance of psycho-emotional health of children and the identification of factors affecting it the purpose of our research is a theoretical analysis and empirical study of the psychological characteristics of the manifestation of fears in preschool children, depending on the type of family. Methods. Theoretical analysis, synthesis, comparison, generalization, interpretation and systematization have been used to clarify the state of development of the problem. Empirical: methods “Fears in the houses” – to identify the most pressing fears of children of preschool age. Results and conclusions. During the analysis of empirical data revealed that the occurrence and manifestation of “age” fears depends on the type of family in which the child lives. Comparative analysis of the results of the empirical research of the characteristics of children’s fears of children from full and single-parent families revealed significant differences in the dominant fears, and therefore the type of family affects the differentiation of dominant fears. Particularly noteworthy is the high percentage in the samples of respondents from single parent families, the indicator of fear of losing relatives, which indicates a problematic situation in the system “parent-child”. In our opinion, high rates of other fears in children from single-parent families indicate a significant emotional imbalance, since they are dominated by irrational fears (fear of darkness, fear of terrible dreams), which do not perform positive functions, only maladapted the child’s psyche, hinder the individual’s development. Lack of communication with the mother or father in consequence of their absence in a single–parent family, leads to dissatisfaction with the need for love and acceptance and, as a consequence a greater vulnerability of the emotional sphere. Unlike respondents from single-parent families, children from full families have socially justified fears (fear of war, military equipment), which indicates an adequate protective reaction to the present. We can assume that communication in the system “husband-wife”, when discussing the painful topics of society, affects the occurrence of fears: war and military equipment of the child.